2018
DOI: 10.1111/sms.13343
|View full text |Cite
|
Sign up to set email alerts
|

Training and match volume and injury in adolescents playing multiple contact team sports: A prospective cohort study

Abstract: Training and competition loads have emerged as valuable injury risk factors but very few studies have explored injury outcomes in adolescent athletes. The aims of this study were to describe injuries and to explore the relationship between training and match load volumes and injury in adolescent athletes participating in multiple contact team sports. One hundred and three male youth rugby athletes aged 14-16 years from 8 rugby union teams were prospectively monitored during a season for weekly training and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Worldwide, burgeoning talent identification (TID) and long-term player development programmes have seen an increased number of male adolescents playing rugby union (rugby, RU) [1,2]. Regardless of playing standard and age category, adolescent RU is a highly demanding physical and skill-based sport characterised by intermittent execution of high-intensity activities such as sprinting and tackling [3][4][5][6][7]. As such, adolescents playing competitive rugby require well-developed physical or physiological qualities and game skills for effective participation.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, burgeoning talent identification (TID) and long-term player development programmes have seen an increased number of male adolescents playing rugby union (rugby, RU) [1,2]. Regardless of playing standard and age category, adolescent RU is a highly demanding physical and skill-based sport characterised by intermittent execution of high-intensity activities such as sprinting and tackling [3][4][5][6][7]. As such, adolescents playing competitive rugby require well-developed physical or physiological qualities and game skills for effective participation.…”
Section: Introductionmentioning
confidence: 99%
“…13,59 Competition, but not training workloads, increases injury risk in youth team sport athletes. 37 A recent study showed a 32% higher match volume in youth rugby players who sustained an injury than those who did not, whereas there were no differences in training volumes between injured and noninjured players. 37 Also, in this study each 1-hour increase in weekly match volume increased injury risk by 41% (odds ratio = 1.41; 95% CI = 1.14-1.74; P = 0.001).…”
Section: Competition To Athletic Development Training Ratiomentioning
confidence: 96%
“…37 A recent study showed a 32% higher match volume in youth rugby players who sustained an injury than those who did not, whereas there were no differences in training volumes between injured and noninjured players. 37 Also, in this study each 1-hour increase in weekly match volume increased injury risk by 41% (odds ratio = 1.41; 95% CI = 1.14-1.74; P = 0.001). One interpretation of these findings is that spending a high proportion of time in competition results in athletes' spending insufficient time preparing physical capacities during training.…”
Section: Competition To Athletic Development Training Ratiomentioning
confidence: 96%
See 2 more Smart Citations